Pemodelan Aplikasi Kasir Untuk Bisnis Fotografi Berbasis Website Menggunakan Rich Picture, PIECES dan UML - Purnomo, Sandi; Handrie Noprison (JSAI (Journal Scientific and Applied Informatics), 2024)
Technological advances have supported the development of cashier systems in business fields (including photography) to improve security and efficiency in business processes. This technological innovation not only streamlines transactions but also increases security measures in the cashier system in the photography business. ARF Studio, which is currently still using a manual system in running its business, is experiencing many obstacles and the creation of a cashier system is expected to overcome the problem. The research location was conducted at ARF Studio with research time in January and February 2024. The web-based cashier application has features for managing transactions, package data, order data, income recap, and printing receipts.